The hot corrosion of nickel-base disc alloys - Potter, Andrew (Cranfield University, 2011)
The efficiency of a jet’s engines has a direct affect on its economic and environmental impact through the quantity of aviation fuel consumed and CO2 emitted. These factors are becoming increasingly important due to higher fuel costs and a greater global awareness of environmental issues. To date, most of the corrosion research work concerning jet turbines has focused on the hottest parts, the turbine blades vanes and combustion chamber. However, as the engines run hotter and with more stress, new superalloys have also been developed for the turbine disc. Although extensive research has been carried out with regard to the mechanical properties of these alloys, relatively little research has been done into their corrosion resistance. The aim of this research is to investigate the hot corrosion characteristics of both the existing and more recently developed disc alloys. Based on these data, the corrosion performance of these alloys was modelled and compared. These aims have been achieved using data from a series of “deposit recoat” corrosion tests on the relevant alloys carried out at Cranfield during the last 6 years. The alloys that are the focus of this study are: Waspaloy, Inconel 718, U720, and RR1000. RR1000 is of particular interest since it is the most recently developed alloy and relatively little is known about its corrosion properties. The tests have been carried over a range of temperatures relevant to the current operating temperatures and the desired higher operating temperatures of the turbine discs. The effects of deposition flux, deposit composition and exposure time have also been investigated as part of this study. A quantitative assessment of the corrosion damage has been carried out and provided metal loss data which has been used to generate empirical models and to compare the effects of variables. The data generated suggest that in the propagation stage of hot corrosion the rate of corrosion is approximately the same between alloys. Therefore the important factor when modelling a disc alloy’s corrosion behaviour is the length of the incubation period. The changes in elemental composition undergone at the alloy surface during corrosion have been investigated using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectroscopy (EDX). The results support the literature in that type II corrosion exhibits no preferential alloy depletion underneath the corrosion deposits.